2021
DOI: 10.1101/2021.12.14.472551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of constraining mediolateral ankle moments and foot placement on the use of the counter-rotation mechanism during walking

Abstract: Stability during walking can be maintained by shifts of the Center of Pressure through modulation of foot placement and ankle moments (CoP-mechanism). An additional mechanism to stabilize gait, is the counter-rotation mechanism i.e. changing the angular momentum of segments around the Center of Mass (CoM) to change the direction of the ground reaction force. It is unknown if and how humans use the counter-rotation mechanism to control the CoM during walking and how this interacts with the CoP-mechanism. Thirte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Other mechanisms are shifting the center of pressure under the stance foot (Reimann et al 2018;van Leeuwen et al 2021) and changing angular momentum around the CoM (Hof 2008;van den Bogaart et al 2020). The increase in EVS-erector spinae muscle coupling during narrow-base walking that we found previously (Magnani et al 2021) suggests that, indeed, angular momentum changes may play a larger role during narrow-base walking, as was also seen in behavioral studies (van den Bogaart et al 2021).…”
Section: Effects Of Walking Conditionsupporting
confidence: 77%
“…Other mechanisms are shifting the center of pressure under the stance foot (Reimann et al 2018;van Leeuwen et al 2021) and changing angular momentum around the CoM (Hof 2008;van den Bogaart et al 2020). The increase in EVS-erector spinae muscle coupling during narrow-base walking that we found previously (Magnani et al 2021) suggests that, indeed, angular momentum changes may play a larger role during narrow-base walking, as was also seen in behavioral studies (van den Bogaart et al 2021).…”
Section: Effects Of Walking Conditionsupporting
confidence: 77%
“…during narrow-base walking that we found previously (Magnani et al 2021), suggests that indeed angular momentum changes may play a larger role during narrow-base walking, as was also seen in behavioral studies (van den Bogaart et al 2021).…”
supporting
confidence: 82%
“…Indeed, we found that the coherence between EVS and erector spinae activity was increased during narrow-base walking. This suggest that the erector spinae muscles are involved in the control of gait stability, possibly by means of changing the angular momentum of the trunk(Hof et al 2007;van den Bogaart et al 2021).…”
mentioning
confidence: 99%
“…Ankle torque and reaction torque (latter from the coordinated motion of the upper body relative to the lower body and also called counter-rotation mechanism) have also been recognized as contributors to ML balance control in humans (7,21,(30)(31)(32)(33)(34)(35)(36)(37). Additionally, variations in actions affecting mainly forward walking progression can also contribute to ML control to the extent that there is crosstalk between sagittal and frontal control mechanisms.…”
Section: Introductionmentioning
confidence: 99%